EXPERIENCE OF RESIDENT PHYSIOTHERAPISTS IN PRIMARY HEALTH CARE: EXPERIENCE REPORT - Vasconcelos , Nara Naone Lino de; Barros, Jonatas Freitas; Silva, Francisco Valter Miranda; Martins , Neilane da Silva; Nunes, Paula Pessoa de Brito (Cadernos ESP, 2024)
To report the experience of the physiotherapist-resident in primary family and community health care in the city of Icapuí through an experience report. This is an experience report, developed based on the work/experience process by the professional, in the municipality of Icapuí in the state of Ceará, in two primary care units (UAPS), from March 2022 to December 2023. It was possible to identify the potential and importance of the residency, as well as the insertion of professional physiotherapists in the ESF, as they work broadly in primary care, knowing the challenges and potential of their work, which will result in an improvement in the quality of the service provided as well as their professional qualifications. It is necessary to include and value the physiotherapist in primary care, for a comprehensive system guaranteeing accessibility for users with physiotherapeutic assistance, as a health promoter together with a qualified and trained team, ensuring greater resolution of health problems.
Keywords: Primary Care; Physiotherapy; Multidisciplinary Residency